Pushover Analysis of Symmetrical and Asymmetrical Buildings With and Without Heavy Loads - Jaweed Jilani Khan, Md; Bellam Sivarama Krishna Prasad, Dr; Seshadri Sekhar.T, Dr (International Journal of Engineering and Technology, 2018)
This Study compares the Structural behavior of buildings constructed on plain ground and on hilly slopes, Firstly by considering normal loads and thereafter by considering heavy loads. The building constructed on plane ground behaves distinctively different from buildings constructed on hilly slopes. Behavior of buildings on plain is simple and symmetrical whereas the buildings on hilly slopes are asymmetrical and irregular in nature. Similarly commercial buildings with normal loading behaves differently in comparison to special buildings with heavy loading. Three different types of Symmetrical and Asymmetrical Analytical ModelsÂ are generated using "ETABS", and are studied under the effect of normal andÂ heavy loads separately by performing Pushover analysis.Â Â